Old-Age Security Reforms in Central-Eastern Europe: The Cases of Czech Republic, Slovak Republic, Hungary and Poland - Mechthild Schrooten; Timothy Michael Smeeding; Gert G. Wagner (Luxembourg Income Study (LIS), 1998)
Our basic question is whether elderly people (pensioners) are among the losers or the winners of the economic transition, in particular in the reforms of the pension systems in Central-Eastern Europe (CEE). The aim of this paper is descriptive. However the descriptive task is not an easy one because we must bring together in one picture two different sources of empirical evidence: On the one hand the national accounts (and official statistics which are underlying the national accounts) and on the other hand evidence by surveys (which are conducted not only by national statistical agencies but by scientific institutes as well) which do not necessarily tell the same story in a straightforward manner.
Keywords: 330; Rentenreform; Tschechische Republik; Slowakei; Ungarn; Polen